Hubungan antara Coping Religiusitas dengan Kecemasan Narapidana Menjelang Masa Bebas di Lembaga Pemasyarakatan Kelas II A Kabupaten Banyuwangi - Alvina Yurizqi Salsabila; Sofyan Hadi (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2022)
Anxiety is one of the most influential factors for individuals, especially those in prison. Field observations have shown that anxiety does not support the mental health of inmates. When an individual's emotions or ego exceed normal limits, they tend to have a greatly influenced attitude. Thus, religious coping is the most influential factor for an individual's mental health in decision-making. This research focuses on investigating whether there is a correlation between religious coping and anxiety among inmates before their release from Class II A Penitentiary in Banyuwangi Regency. This research is a quantitative study with a correlational analysis approach. The sample was determined using purposive sampling technique. The data were collected by distributing questionnaires and analyzed using Pearson Product Moment correlation. The study found that 62.9%, or 22 inmates, had a high level of religious coping, while 25.7%, or 9 other inmates, still had anxiety before their release from Class II A Penitentiary in Banyuwangi Regency. These results proved that the level of anxiety among inmates was lower than their level of religious coping. The findings also showed that there was a significant correlation between religious coping and anxiety among inmates before their release from Class II A Penitentiary in Banyuwangi Regency, with a Pearson correlation of -0.433 and a significance level (p) of 0.009, which means P > 0.05. In other words, if an inmate's religious coping increases, it will reduce their anxiety, and vice versa.